Bio-pest control for pigeon pea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Pigeon pea is an interesting crop as it can be grown and thrive in many different cropping situations. There are short duration and perennial cultivars. It is intercropped with cereals, with cotton, with other legumes and it has even been grown on...